Prevalence of Group B Streptococcus in Vagina and Rectum of Pregnant Women of Islamic & Non-Islamic Countries: A Sys-tematic Review and Meta-Analysis - Fatemeh Abbasalizadeh; Sajjad Pourasghary; Maryam Shirizadeh; Sanaz Mousavi; Morteza Ghojazadeh; Hossein Hoseinifard; Fatemeh Salehnia; Leila Nikniaz (Tehran University of Medical Sciences, 2021)
Background: Group B streptococcus or streptococcus Agalactia is a gram positive beta hemolytic bacteria which is the main factor in neonatal infections. This study aimed at determining the prevalence of GBS in world and clarifying the rate of this infection in Islamic and non-Islamic countries. Methods: We performed a systematic search by using different databases including Medline, Scopus, Science Direct, Psycho-Info ProQuest and Web of Science published up to Feb 2019. We undertook meta-analysis to obtain the pooled estimate of prevalence of GBS colonization in Islamic and non-Islamic countries. Results: Among 3324 papers searched, we identified 245 full texts of prevalence of GBS in pregnancy; 131 were included in final analysis. The estimated mean prevalence of maternal GBS colonization was 15.5% (CI:95% (14.2-17)) worldwide; which was 14% (CI:95% (11-16.8)) in Islamic and 16.3% (CI:95% (14.6-18.1)) in non-Islamic countries and was statistically significant. Moreover, with regards to sampling area, prevalence of GBS colonization was 11.1 in vagina and 18.1 in vagina-rectum. Conclusion: Frequent washing of perineum based on religious instructions in Islamic countries can diminish the rate of GBS colonization in pregnant women.